THE FIRST YEAR OF THE SUBJECT COMPETITION CALLED THE TECHNICAL OLYMPICS - SIRKA, Jan (Trends in education, 2011)
Department of Technology and Information Technologies at the Faculty of Education of Constantine the Philosopher University in Nitra asked the Ministry of Education of the Slovak Republic to register the subject competition into the group of subject vocational Olympics and promotion competitions with the aim to increase an interest in teaching the subject Technical Education at elementary schools. There was the first year of this kind of competition in 2010/2011. In the contribution, the author summarized and analyzed the course and results of the regional, district and all-Slovak rounds of the technical Olympics.
Keywords: competition; technical Education; technical Olympics.